ANALISIS PERHITUNGAN HARGA POKOK PRODUKSI MENGGUNAKAN METODE VARIABLE COSTING PADA PT. CELEBES MINAPRATAMA BITUNG - Kiay, Dewi Sartika; Morasa, Jenny; Pontoh, Winston (GOING CONCERN : JURNAL RISET AKUNTANSI, 2013)
Cost of Production is a collection of the costs incurred to process raw materials into finished materials. This study aims to determine the analytical calculation of the cost of production of fish processing wood at PT. Celebes Minapratam Bitung. This company is a manufacturing company was not immune from the problem and the calculation of production costs in determining the cost of production companies using the full cost method of separating elements where production costs are variable and fixed yet done. This has led to inaccuracies in the calculation of the cost of the product will affect the determination of the selling price and profit. The data analysis penlelitian ie, production processes, material cost report, report labor costs, overhead cost report. The results of determining the cost of production using the method in which the cost is calculated based on the full cost method is better according to the method of calculation used variable costing. This results in differences that affect the determination of the selling price. For that the company should separate the production costs resulting in proper production costs.